2016
DOI: 10.1186/s12936-016-1490-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection of N86F184D1246 haplotype of Pfmrd1 gene by artemether–lumefantrine drug pressure on Plasmodium falciparum populations in Senegal

Abstract: Background The use of artemisinin as a monotherapy resulted in the emergence of artemisinin resistance in 2005 in Southeast Asia. Monitoring of artemisinin combination therapy (ACT) is critical in order to detect and prevent the spread of resistance in endemic areas. Ex vivo studies and genotyping of molecular markers of resistance can be used as part of this routine monitoring strategy. One gene that has been associated in some ACT partner drug resistance is the Plasmodium falciparum multidrug resistance prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
6
31
2
Order By: Relevance
“…AL also selects for other pfmdr1 haplotypes, like the NYD, which showed a steady increase in frequencies between temporal populations ( 39 ). This is consistent with studies in West Africa that found selection of these haplotypes by AL ( 40 42 ). Considering the risk to AL efficacy, an extended study of the temporal trends and association of these alleles with drug efficacy as parasite prevalence reduces could guide policy on ACTs in The Gambia.…”
Section: Discussionsupporting
confidence: 92%
“…AL also selects for other pfmdr1 haplotypes, like the NYD, which showed a steady increase in frequencies between temporal populations ( 39 ). This is consistent with studies in West Africa that found selection of these haplotypes by AL ( 40 42 ). Considering the risk to AL efficacy, an extended study of the temporal trends and association of these alleles with drug efficacy as parasite prevalence reduces could guide policy on ACTs in The Gambia.…”
Section: Discussionsupporting
confidence: 92%
“…In multivariate analysis, none of the Pfmdr1 alleles had no significant association with treatment failure or risk of new-infections after treatment with ASAQ. In AL treatment arm, patients harbouring Pfmdr1 -184F had significantly higher risk of new-infection, in line with a study that reported an association between lumefantrine and Pfmdr1 F184 in ex-vivo assay [ 32 ]. Interestingly, patients with anemia were increasingly at high risk of recrudescence in AL treatment arm, this may be supported the fact that the risk of acquiring anaemia is high in patients with high parasite density (<200,000/μL)) which was shown to be an independent risk factor for clinical treatment failure by up to 60% for the different antimalarial treatment[ 33 ].…”
Section: Discussionsupporting
confidence: 84%
“…An association was found between the presence of the 76T allele and the decrease in sensitivity to chloroquine (p = 0.0195) but not to amodiaquine (0.0539) and piperaquine (0.9370). A decrease in ex vivo sensitivity and an increase in the prevalence of the N86Y mutation relationship was not significantly found with amodiaquine (p = 0.5290) and the geometric mean for piperaquine was very low compared to that found in other countries [3034]. These compounds are currently used in combination with dihydroartemisinin for piperaquine, SP and artesunate for amodiaquine.…”
Section: Discussionmentioning
confidence: 92%